Elucidation of the biochemical mechanism of glycogen phosphorylation in Escherichia coli - Nepembe, Mehafo, Ndafapawa (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Genetics. Plant Biotechnology)--University of Stellenbosch, 2009.